Code-Mixing Practices of EFL Lecturers in Classroom Settings - Victor; Pongsapan, Nehru P; Allo, Markus Deli Girik (Institut Agama Islam Negeri Palopo, 2024)
The objevtive of research is to find out what type of code mixing used by EFL lecturers in Classroom Contex and what the impact are use code mixing used by EFL lecturers in classroom context. The researcher conducted this investigation used qualitative methodologies. Purposive sampling technique for the participant lecturers and snowball sampling for the students at campus 1 UKI Toraja. Observation and interview are the instruments of this research. The findings show that there are four types of code mixing used, namely insertion, alternation, congruent lexicalization, and involving a change in pronunciation. The impact of using code mixing is incredibly positive, with students reporting increased understanding, motivation, and engagement in the learning process. However, there are also concerns that dependence on code mixing may reduce students' motivation to learn English independently. This research emphasizes the importance of a balanced teaching strategy to effectively support students' language development. In conclusion, the research shows four types of code-mixing insertion, alternation, congruent lexicalization, and involving a change in pronunciation. Each contributing positively to students' understanding, motivation, and engagement in learning. However, reliance on code mixing may hinder students' independent learning of English. Therefore, a balanced teaching strategy is essential to effectively support students' language development. Keywords: Sociolinguistics, Code Mixing, EFL Lecturers, Impact, Multilingualism